Weaned piglets prefer feed with hydroxychloride trace minerals to feed with sulfate minerals - Van Kuijk, Sandra J A (Transl Anim Sci, 2019)
The aim of this study was to determine whether newly weaned piglets had a preference for diets containing hydroxychloride trace minerals (HTM). To test this, two preference tests were set up. In Exp. 1, the piglets could choose between HTM or inorganic, originating from sulfate trace minerals (STM) in the form of sulfates. Two treatments were applied with high Cu levels (160 ppm Cu added) or low Cu levels (15 ppm Cu added). All diets contained 110 ppm added Zn from the same source as Cu in the respective diet. The pigs could choose between a diet with hydroxychloride Cu and Zn or with Cu and Zn originating from sulfates at the same mineral levels. The piglets were included in the study from weaning until 34 d after weaning. In Exp. 2, the piglets could also choose between HTM and STM. However, automated feeding stations were used to collect individual feed intake data. Similarly two treatments were applied, one with high Cu levels (160 ppm added Cu) and one with slightly lower Cu levels (140 ppm added Cu until 28 d after weaning, thereafter 15 ppm added Cu). All diets contained 110 ppm added Zn from the same source as Cu in the respective diet. The piglets were followed until 35 d after weaning. The current studies showed that when piglets were given a choice, they preferred diets with HTM. This effect resulted only in a significant (P < 0.05) preference for HTM at high dietary Cu levels (160 ppm) ranging from 76% to 81% in the first and second week of Exp. 1 to between 53.4% and 57.8% in the overall experiment period of Exp. 2. This preference was less pronounced at levels of 140 ppm added or less. Individual feed intake and gain measurements did not show any link between the preference and the performance.